Efektivitas Pendampingan Penyusunan Instrumen Penilaian Sikap bagi Guru SD - Mawardi Mawardi; Agustina Tyas Asri Hardini (Jurnal Pengabdian Pada Masyarakat, 2020)
EFFECTIVENESS OF MENTORING INSTRUMENT PREPARATION OF ATTITUDE ASSESSMENT FOR ELEMENTARY SCHOOL TEACHERS. The purpose of devotion to society in the form of this training is to increase the competence of elementary school teachers in THE KKG Group of Dr. Wahidin Soediro Hoesodo District, Central Java in order to develop a scale instrument of attitude. The benefits gained by the participants in this training and mentoring are the increasing understanding and experience for the teacher in organizing the instrument of attitude. This activity is implemented by the following steps: 1) Identifying the ability of the trainees, 2) sets the need Gap, 3) develops the program, 4) conducting the training, and 5) evaluation. Based on the findings of the training as described above, the following steps included : 1) The training on the preparation of attitude assessment instruments is an urgent necessity; 2) The average Pretest score in training only reaches 54; While on final test reached 69.76. A minimum score pretest 23 and final test 47; Maximum score pretest 72 and final test 79. The increase in the achievement of the learning outcomes is quite meaningful, both seen from the average and from the achievement of the maximum score of 79; 3) found data from 25 elementary school teachers who attended the training, 16 of them (68%) has uploaded training products in the form of Likert model scale instrument. Compared to the specified PM target of 60%, this achievement has exceeded the target.